2021
DOI: 10.5114/wo.2021.105969
|View full text |Cite
|
Sign up to set email alerts
|

The role of complementary and alternative methods in the treatment of pain in patients with cancer – current evidence and clinical practice: a narrative review

Abstract: Introduction Pain related to cancer, despite the numerous treatment options available, is still a challenge in contemporary pain medicine. The unsatisfactory treatment of cancer pain is one of the main reasons why patients seek complementary and alternative methods (CAM) and a more integrative/holistic approach to pain management. The popularity of CAM forces healthcare professionals to provide patients with current and evidence-based information on the effectiveness and safety of CAM. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In the literature, alternative therapies for managing post-hemorrhoidectomy pain included transcutaneous electrical nerve stimulation (TENS) and acupuncture. These non-pharmacological interventions aim to modulate neurotransmitters along the nociceptive pathway to reduce hyperalgesia [ 86 ]. TENS on the dorsal web between the first and second metacarpal bone and on the radial side of forearm was shown to reduce pain and opioid consumption after hemorrhoidectomy [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, alternative therapies for managing post-hemorrhoidectomy pain included transcutaneous electrical nerve stimulation (TENS) and acupuncture. These non-pharmacological interventions aim to modulate neurotransmitters along the nociceptive pathway to reduce hyperalgesia [ 86 ]. TENS on the dorsal web between the first and second metacarpal bone and on the radial side of forearm was shown to reduce pain and opioid consumption after hemorrhoidectomy [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent comprehensive narrative review regarding using CAM treatments for cancer pain, the study stated that a multimodal approach to cancer pain management, including herbal medicines, might improve the quality of pain treatment and patients' quality of life. 59 Moreover, a pilot study describes a multimodal outpatient Patients who had received an herbal combination gained 0.9 kg weight, compared with a weight loss of 0.53 kg in the placebo group (P < .001). Improvement in quality of life and FAACT scores were not significant in each group (P > .05); the Edmonton symptom assessment scale questionnaire assessment indicated that there was a significant improvement in two indices in the intervention group, including appetite (P < 0.001) and fatigue (P = .008).…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent comprehensive narrative review regarding using CAM treatments for cancer pain, the study stated that a multimodal approach to cancer pain management, including herbal medicines, might improve the quality of pain treatment and patients’ quality of life. 59 Moreover, a pilot study describes a multimodal outpatient complementary therapy program including herbs, conducted during adjuvant radiotherapy and/or chemotherapy or outpatient aftercare, showing its potential to improve the overall quality of life and reduce treatment-associated adverse effects. 60…”
Section: Discussionmentioning
confidence: 99%
“…Music therapy has no side effects and can be applied together with other clinical interventions (Valero-Cantero et al, 2020). The American Society of Clinical suggests that music therapy can be used as a treatment to reduce pain or soreness in cancer patients (Kocot-Kępska et al, 2021). The use of music therapy requires only a small fee.…”
Section: Discussionmentioning
confidence: 99%